Language Assessment : Principles and Classroom Practices - Brown, H.Douglas (Pearson Education, Inc., 2019)
Language Assessment: Principles and Classroom Practices is designed to offer a comprehensive survey of essential principles and tools for second language assessment. Its first and second editions have been successfully used in teacher-training courses, teacher certification curricula, and TESOL master of arts programs. As the third in a trilogy of teacher education textbooks, it is designed to follow H. Douglas Brown’s other two books, Principles of Language Learning and Teaching (sixth edition, Pearson Education, 2014) and Teaching by Principles(fourth edition, Pearson Education, 2015). References to those two books are made throughout the current book. Language Assessment features uncomplicated prose and a systematic, spiraling organization. Concepts are introduced with practical examples, understandable explanations, and succinct references to supportive research. The research literature on language assessment can be quite complex and assume that readers have technical knowledge and experience in testing. By the end of Language Assessment, however, readers will have gained access to this not-so-frightening field. They will have a working knowledge of a number of useful, fundamental principles of assessment and will have applied those principles to practical classroom contexts. They will also have acquired a storehouse of useful tools for evaluating and designing practical, effective assessment techniques for their classrooms.